2018
DOI: 10.1002/erv.2661
|View full text |Cite
|
Sign up to set email alerts
|

High‐intensity exercise is associated with a better nutritional status in anorexia nervosa

Abstract: Objective Our aim is to investigate the links between duration and intensity of exercise and the nutritional status in terms of body composition in acute anorexia nervosa (AN) patients. Method One hundred ninety‐one hospitalized women suffering from AN were included. Exercise duration and intensity were assessed using a semistructured questionnaire. Body composition was measured using bioelectrical impedance. Linear multiple regression analyses were carried out using body mass index, fat‐free mass index, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
1
12
0
1
Order By: Relevance
“…Moreover, we found that ABA-R mice actually eat more than FR-R mice and consequently gain more weight, despite the energy expenditure from wheel running. Though counterintuitive, this parallels evidence from clinical studies demonstrating that appropriate exercise may be beneficial in clinical treatment (46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, we found that ABA-R mice actually eat more than FR-R mice and consequently gain more weight, despite the energy expenditure from wheel running. Though counterintuitive, this parallels evidence from clinical studies demonstrating that appropriate exercise may be beneficial in clinical treatment (46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 75%
“…However, a substantial body of evidence supports the implementation of exercise interventions for people with mental illnesses (Stanton & Happell, 2013; Zschucke, Gaudlitz, & Strohle, 2013), including eating disorders (Hausenblas, Cook, & Chittester, 2008; Vancampfort et al, 2013) and AN in particular (Fernández del Valle et al, 2010; Fernández del Valle, Larumbe, Morandé, & Perez, 2016; Moola, Gairdner,& Amara, 2013; Ng, Ng, & Wong, 2013; Noetel et al, 2016; Rizk et al, 2019). For example, Fernández del Valle et al (2016) analysed the effects of short‐term resistance training on body composition and muscle function in AN restrictive‐type patients.…”
Section: Introductionmentioning
confidence: 99%
“…AN treatment recommendations from the American Psychiatric Association and the National Institute for Health and Clinical Excellence Eating Disorders Guideline include nutritional rehabilitation, psychosocial interventions, family interventions and pharmacotherapy (although there is limited evidence supporting the use of HIGHLIGHTS � This systematic review highlights the paucity of data to make decisions about the relevance of structured and supervised exercise as a treatment in patients with anorexia nervosa (AN) � Supervised physical exercise interventions were not associated with weight loss in patients with AN � Physical exercise interventions focused on resistance/strength or flexibility have no additional effect on anthropometry, but they might improve vital signs, muscle function and strength, and eating disorder symptomatology � Physical exercise programmes have not shown significant effects on psychological variables such as anxiety and depression medication to treat chronic AN or to restore weight and prevent relapse). However, a substantial body of evidence supports the implementation of exercise interventions for people with mental illnesses (Stanton & Happell, 2013;Zschucke, Gaudlitz, & Strohle, 2013), including eating disorders (Hausenblas, Cook, & Chittester, 2008;Vancampfort et al, 2013) and AN in particular (Fernández del Valle et al, 2010;Fernández del Valle, Larumbe, Morandé, & Perez, 2016;Moola, Gairdner,& Amara, 2013;Ng, Ng, & Wong, 2013;Noetel et al, 2016;Rizk et al, 2019). For example, Fernández del Valle et al (2016) analysed the effects of short-term resistance training on body composition and muscle function in AN restrictive-type patients.…”
mentioning
confidence: 99%
“…In addition to antidepressants, voluntary exercise as well as lactate, a metabolite produced during exercise, promote resilience to CSDS and anxiety disorders (Karnib et al, 2019; Mattar et al, 2017; Mul, 2018; Mul et al, 2018; Rizk et al, 2018) and increase BDNF signaling. Multiple reports have deciphered the exercise-regulated molecular pathways responsible for hippocampal BDNF activation and identified the PGC1a/FNDC5 as a major BDNF inducer (El Hayek et al, 2019; Sleiman et al, 2016; Wrann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%